2020
DOI: 10.7759/cureus.7766
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Shock from Subcutaneous Implantable Cardioverter-Defibrillator Caused by Electrical Remodeling After Wolff-Parkinson-White Ablation

Abstract: Hypertrophic cardiomyopathy (HCM) and Wolff-Parkinson-White syndrome have been associated with sudden cardiac death. A subcutaneous implantable cardioverter-defibrillator (S-ICD) is an effective device used to reduce the risk of sudden cardiac death in these patients. The most common cause of inappropriate shocks with S-ICD is T-wave oversensing. We present the case of a 19-year-old man with repeated shocks from his S-ICD. This case highlights some of the sensing issues related to the S-ICD that can result in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In our case, there was an oversensing of only T waves. Oranus et al reported a case of TWOS due to a change in the electrical vector following T wave remodeling and progression of the hypertrophic obstructive cardiomyopathy (HOCM) scar, causing loss of R waves in a 19-year-old male with a history of HOCM and Wolff-Parkinson-White (WPW) syndrome [ 12 ]. A similar case of cardiac remodeling leading to uncorrectable T wave oversensing was reported by Saleem et al [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, there was an oversensing of only T waves. Oranus et al reported a case of TWOS due to a change in the electrical vector following T wave remodeling and progression of the hypertrophic obstructive cardiomyopathy (HOCM) scar, causing loss of R waves in a 19-year-old male with a history of HOCM and Wolff-Parkinson-White (WPW) syndrome [ 12 ]. A similar case of cardiac remodeling leading to uncorrectable T wave oversensing was reported by Saleem et al [ 13 ].…”
Section: Discussionmentioning
confidence: 99%